2007
DOI: 10.1177/112067210701700621
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Bevacizumab for Retinal Angiomatous Proliferation Associated with Retinal Pigment Epithelial Detachment

Abstract: Systemic bevacizumab therapy appears to be safe and effective in the treatment of RAP associated with PED during this short follow-up period of 3 months. The authors recommend a large trial with long-term follow-up to confirm the promising results and evaluate the occurrence of adverse effects associated with systemic bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The results showed no difference in final visual acuity, but the thickness of the retina, as measured by OCT, was diminished in the treatment group. Other studies have found a similar efficacy with systemic therapy as well 13 14…”
supporting
confidence: 55%
See 1 more Smart Citation
“…The results showed no difference in final visual acuity, but the thickness of the retina, as measured by OCT, was diminished in the treatment group. Other studies have found a similar efficacy with systemic therapy as well 13 14…”
supporting
confidence: 55%
“…Concurrently, there has been a thread in the ophthalmic literature of small case series and case reports involving the systemic use of anti-vascular endothelial growth factor (VEGF) antibodies either purposefully for ocular disease or in cases where patients had a systemic cancer in combination with ocular neovascularisation or macular oedema with apparent success 1114…”
mentioning
confidence: 99%
“…Intravitreal antiangiogenic drugs have been used to treat CNV secondary to AMD for the past 3 years. However, the use of antivascular endothelial growth factor (anti-VEGF) drugs to treat RAP lesions was not reported until 2007 (13).…”
Section: Discussionmentioning
confidence: 99%
“…12 Before the introduction of anti-vascular endothelial growth factor (anti-VEGF) agents, there were many different therapeutic approaches for the management of RAP, including photodynamic therapy (PDT), 4,13-15 surgical ablation of retinal feeding arterioles and draining venules, [16][17][18] transpupillary thermotherapy, 19 focal laser photocoagulation, 20 focal laser combined with intravitreal triamcinolone (IVT), 21,22 or PDT in combination with triamcinolone, 8,15,[23][24][25][26][27] but they often had disappointing results. Recent studies have reported short-term promising results using anti-VEGF agents, the current standard care for wet agerelated macular degeneration, 7,8,[28][29][30][31][32][33] or a combination of anti-VEGF agents and PDT. 8,34,35 Among these studies, we have published our preliminary results of a prospective study comparing 3 therapeutic modalities against RAP, that is, ranibizumab, ranibizumab in combination with PDT, and IVT in conjunction with PDT, with mean follow-up of 8.4, 14, and 16.4 months for each group, respectively.…”
mentioning
confidence: 98%